Poly(ADP‐ribose) Polymerase 1 (PARP1) in Atherosclerosis: From Molecular Mechanisms to Therapeutic Implications. Issue 3 (3rd September 2013) - Xu, Suowen; Bai, Peter; Little, Peter J.; Liu, Peiqing
Abstract: Poly(ADP‐ribosyl)ation reactions, carried out by poly(ADP‐ribose) polymerases (PARPs/ARTDs), are reversible posttranslational modifications impacting on numerous cellular processes (e.g., DNA repair, transcription, metabolism, or immune functions). PARP1 (EC 2.4.2.30), the founding member of PARPs, is particularly important for drug development for its role in DNA repair, cell death, and transcription of proinflammatory genes. Recent studies have established a novel concept that PARP1 is critically involved in the formation and destabilization of atherosclerotic plaques in experimental animal models and in humans. Reduction of PARP1 activity by pharmacological or molecular approaches attenuates atherosclerotic plaque development and enhances plaque stability as well as promotes the regression of pre‐established atherosclerotic plaques. Mechanistically, PARP1 inhibition significantly reduces monocyte differentiation, macrophage recruitment, Sirtuin 1 (SIRT1) inactivation, endothelial dysfunction, neointima formation, foam cell death, and inflammatory responses within plaques, all of which are central to the pathogenesis of atherosclerosis. This article presents an overview of the multiple roles and underlying mechanisms of PARP1 activation (poly(ADP‐ribose) accumulation) in atherosclerosis and emphasizes the therapeutic potential of PARP1 inhibition in preventing or reversing atherosclerosis and its cardiovascular clinical sequalae.